Poly (N‐acryloxysuccinimide‐co‐ethylene glycol dimethacrylate) precursor monolith and its post polymerization modification with alkyl ligands, trypsin and lectins for reversed‐phase chromatography, miniaturized enzyme reactors and lectin affinity chromatography, respectively. Issue 22 (14th September 2017) - Jonnada, Murthy; El Rassi, Ziad
Abstract: This investigation was aimed at introducing a monolithic precursor that can be conveniently grafted with the desired chromatographic ligand via the process of post polymerization modification (PPM). The precursor was obtained by the in‐situ polymerization of N ‐acryloxysuccinimide (NAS) and ethylene glycol dimethacrylate (EDMA) in a narrow bore stainless steel column of 1 mm i.d. yielding a poly(NAS‐co‐EDMA) monolithic column designated as the poly(NAS‐co‐EDMA) monolith (NASM) column. In a first PPM, the NASM column was bonded with octadecyl (OD) ligands yielding a nonpolar NASM‐OD column that proved useful for reversed phase chromatography (RPC) of proteins in gradient elution at increasing %ACN in the mobile phase. NASM‐OD resulted from the reaction between the N ‐hydroxysuccinimide of NASM with octadecyl amine. In a second PPM, NASM was surface immobilized with trypsin generating a proteolytic narrow bore enzyme reactor called NASM‐trypsin immobilized enzyme reactor (IMER) that permitted the online digestion of proteins in a 20‐min single pass through the IMER incorporated in a setup equipped with a short RPC column to achieve simultaneously a peptide tryptic map. This constituted a rapid turnover whereby ∼95% of the protein was hydrolyzed by the immobilized trypsin. In a third PPM, the NASM column was surface immobilized with three different lectins (LCA, Con A and RCA) having complementary affinities toward serum glycoproteins thus permitting the capture of a wide range of glycoproteins/glycoforms. The three NASM‐lectin columns when operated in a tandem format led to assessing the level of the various glycoforms in human serum via LC‐MS/MS analysis of the captured protein fractions by each NASM‐lectin column.